Proceedings of the thirteenth world petroleum congress - World Petroleum Congress (13th : 1991 : Buenos Aires, Argentina) (Chichester, NY : John Wiley & Sons, 1992)
v.1 Organization, plenary addresses and indexes -- v. 2. Exploration and production -- v.3. Processing and products -- Reserves, management, finance and general